Classification and integration of knowledge: the Qur’ānic educational model - Surajudeen, Ahmad Tijani; Awang Mat , Muhamad Zahiri (Revelation and Science, IIUM, 2013)
The contemporary Muslim Ummah undeniably has been swimming in the ocean of educational dilemma which henceforth contributes to spiritual, social, economic and political confusions. Disunity, disintegration between Revealed and non-Revealed knowledge integrally and immensely contributed to this dilemma. The scriptural manual of guidance, the Qur’ān has been neglected from being the basis of educational policy and curriculum among a vast majority of Muslims. Early 1970s was a turning for an intellectual discourse to get rid of these dilemmas that affect all facets of Muslim Ummah’s endeavours. Several studies such as: Abdullah (1982); Abu Sulayman (1994); Rosnani (2008); Sidek (2009); Ahmad & Awang Mat (2011) etc. have posited that for Muslims to get rid of these challenges, their educational system must be formulated on the basis of Islamic philosophy of education more essentially putting more emphasis on the Qur’ānic paradigm and unification of religious sciences (ʽIlm naqlī) and non-religious sciences (ʽIlm ʽaqlī). Various scholarly studies such as Osman Bakar (2006) have examined the classical works on the classification and integration of religious and non-religious knowledge. Little focus of attention is given to deeply explain the classification and integration of knowledge among the contemporary Muslims by considering the Qur’ānic model and tawhīdic paradigm. This paper primarily aims at examining the classification and integration of knowledge from the Qur’ānic model view-lens. The paper is library-based whereby both primary and secondary sources are extensively analyzed. The methodology used in the paper is document analysis, descriptive and analytical approaches on the Scriptural Book, chapters 62:2 and 96:1-5 are painstakingly analyzed. The epistemological and philosophical issues relating to the classification and integration of knowledge are also explicitly elaborated. The finding from the Qur’ānic model of classification and integration of knowledge with particular reference to Q62:2 and Q96:1-5 compartmentally identified three divisions of knowledge namely: religious, pure and natural sciences. The identified divisions specifically are in relation to the signs (ayātu manzūr and ayātu mantūq) which form the epistemological foundation of Qur’ānic and tawhīdic paradigms of integration of knowledge among the contemporary Muslims. It is thereby recommended that, for Muslims to revive the intellectual success of classical Islamic civilization and contributions of contemporary Muslim scholars to all branches of knowledge, it is essentially paramount to be cognizance of creative ideas embodied in the Holy Qur’ān.